Temporal Lobe Malformations and Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
Temporal lobe developmental malformations (TLDM) (focal cortical dysplasia and balloon cells) occurred with mesial temporal sclerosis as dual pathologies in 87% of 30 patients with unilateral TLDM and intractable partial epilepsy treated at the UAB Epilepsy Center, University of Alabama at Birmingham, AL.